2017
DOI: 10.3928/01477447-20170810-02
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Unicortical Stress Risers of the Proximal Humerus Associated With Pectoralis Major Repair

Abstract: Proximal humerus fracture after pectoralis major tendon repair has been recently reported. Although this complication is rare, it may be possible to decrease such risk using newer techniques for myotenodesis. This study was designed to evaluate various unicortical stress risers created at the proximal humeral metadiaphysis during myotenodesis for repair of pectoralis major ruptures. A simulated pectoralis major myotenodesis was performed using fourth-generation Sawbones (N=30). Using previously described anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…12,37 Other studies have found varying results when comparing bone trough repairs with suture anchor repairs, with 1 reporting that bone trough repairs were stronger and another reporting that bone trough techniques may increase postoperative fracture risk. 34,39 Wilson et al 39 found that unicortical button fixation with larger caliber suture and suture tape may provide superior construct strength compared with transosseous suture repairs. 39 The interval between injury and surgery may have an impact on the outcome after pectoralis major tendon repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,37 Other studies have found varying results when comparing bone trough repairs with suture anchor repairs, with 1 reporting that bone trough repairs were stronger and another reporting that bone trough techniques may increase postoperative fracture risk. 34,39 Wilson et al 39 found that unicortical button fixation with larger caliber suture and suture tape may provide superior construct strength compared with transosseous suture repairs. 39 The interval between injury and surgery may have an impact on the outcome after pectoralis major tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…34,39 Wilson et al 39 found that unicortical button fixation with larger caliber suture and suture tape may provide superior construct strength compared with transosseous suture repairs. 39 The interval between injury and surgery may have an impact on the outcome after pectoralis major tendon repair. 5 While several included studies have noted marginally better functional outcomes after acute repairs compared with chronic repairs, 1,2,26,35 none of the included studies indicated statistically significantly improved outcomes in acute repairs, although the majority of studies were not sufficiently powered to show differences between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Wilson et al. 16 performed a biomechanical study testing the effects of cortical defects on the humeral diaphysis. Their study compared the effect of a 5-mm × 40-mm bone trough, two 7-mm × 15-mm biocomposite interference screws, and three 2.9-mm unicortical suture anchors.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal humeral shaft fractures may occur at the site of bone troughs and cortical drill holes after a pectoralis tendon rupture repair. 15 Wilson et al 16 performed a biomechanical study testing the effects of cortical defects on the humeral diaphysis. Their study compared the effect of a 5-mm  40-mm bone trough, two 7mm  15-mm biocomposite interference screws, and three 2.9-mm unicortical suture anchors.…”
Section: Pectoralis Major Intramedullary Anchor Repair E879mentioning
confidence: 99%
See 1 more Smart Citation